Analysis of Post Pandemic Covid-19 Students' Activities - Dedi Supriadi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Physical activity is an activity of the body that is carried out systematically and purposefully, both preventive and curative. The purpose of this study was to analyze by knowing how the level of physical activity of students was during the post-covid-19 pandemic. The research method applied is a quantitative descriptive with a survey approach. The subjects in this study were all 32 students of Class X-2 SMA Pasundan 2 Cimahi City. The instrument used was using a questionnaire about physical activity which only took two types of activity out of three types of activity, namely activity during exercise and during free time. The data analysis technique uses a survey quantitative analysis type, namely the proportion technique. From the results of the study  it is known that the physical activity index of students when exercising gets an average score of 2.96 which is included in the less active category, while the physical activity index in their free time has a score of 3.30 which is included in the moderately active category. This indicates that more physical activity is carried out in students' free time than during sport.